Differences in Growth and Calcification Rates in the Reef-Building Coral Porites lobata: The Implications of Morphotype and Gender on Coral Growth - Tortolero-Langarica, José de Jesús A.; Cupul-Magaña, Amílcar L.; Carricart-Ganivet, Juan. P.; Mayfield, Anderson B.; Rodríguez-Troncoso, Alma P. (Frontiers in Marine Science, 2016)
Corals display different growth forms as an adaptive response to both local and global environmental conditions. Despite the importance of morphologic variability on corals, growth and calcification rates of different coral morphotypes have been poorly recorded in the Eastern Pacific. The purpose of this study was to compare annual extension rate (cm yr-1), skeletal density (g cm-3), calcification rate (g cm-2 yr-1) and tissue thickness (mm) of males and females colonies in three different morphotypes of the common reef-building coral Porites lobata; columnar, massive, and free-living (corallith) forms. The results show significant differences in all 4-growth parameters between morphotypes over a 6-year interval, and also differences between males and females in most morphotypes. Massive colonies presented 15-33% faster annual rates compared with columnar and free-living. Male colonies showed 30-40% faster annual rates than females for both columnar and corallith morphologies. These data exhibit the extensive plasticity of this species and highlight the fact that each morphotype x gender group produced a different physiological response to environmental conditions. Therefore, these information reveal that P. lobata from the Eastern Tropical Pacific develops different morphologies to allow it to maintain coral species population, characteristics that enhance the species possibility to further its distribution across the reef-framework